Fungal pyogranulomatous encephalitis in a dog with leishmaniosis - Machado,Gisele Fabrino (2006)
A case of pyogranulomatous micotic encephalitis in a one-year old, female, Fila Brasileiro dog is reported. Gross examination of the cerebrum revealed a softened haemorrhagic area in the right frontal cortex and on the cut surface of the left hemisphere, which affected the white matter and deep cortical areas. The diagnosis of multifocal mycotic pyogranulomatous encephalitis was obtained by the histopathological examination, which showed the presence of macrophages, giant cells, haemorrhage and brownish septate hyphae diffusely distributed within the tissue and invading vessel lumina. Identification of amastigotes forms in popliteus lymphonode imprint confirmed infection by Leishmania sp. Mycotic infection in the brain of this dog was related to a concurrent leishmaniosis, an immunosuppressive disease.